KAJIAN DOSIS TRICHODERMA SP. DAN PUPUK ORGANIK PADA PERTUMBUHAN DAN HASIL TANAMAN STEVIA (Stevia rebaudiana Bertoni M) - Setie Harieni (JURNAL ILMIAH AGRINECA, 2014)
This study entitled of dose Trichoderma sp. and Organic Fertilizer On Growth And Yield Of Stevia (Stevia rebaudiana Bertoni M), in the rural districts Nglurah Tawangmangu, Karanganyar. This study used a factorial method with RCBD ( Randomized Complete Block Design)  consists of two factors , the first factor dosing Trichoderma sp. ( T ) consists of 4 levels namely : T0 : 0 g/plant , T1 : 25 g/plant, T2 : 50 g/plant, T3 : 75 g/plant. The second factor of organic fertilizer (manure) ( K ) dose of cow manure consists of 3 levels : K1 : 200 g/plant, K2 : 250 g/plant, K3 : 300 g/plant, from two to 12, the combination of these factors was obtained and repeated 3 times. The results of this study were dose of Trichoderma sp. and  cow manure  real effect and the interaction of the two treatments showed significant results on tiller number, stover fresh weight, dry stover weight, fresh weight per plot and the dry weight per plot but not significant effect on plant height. Dose Trichoderma sp. of 75 g and 250 g cow manure (T3K2) give the best results in the stevia plant dry weight per plot results 1900 g.